The Performance of Beethoven’s “Diabelli Variations”. Continuity, Discontinuity, Cyclic Integration, Irony - William Kinderman (Olms (only printed volumes 2003-2017), 2021)
This essay explores the performance challenges of Beethoven’s “Diabelli Variations”; it is paired with the author’s own studio recording of the work coordinated with the musical score. The commentary seeks to address issues of compositional genesis, motivic development, musical character, and formal shaping, while keeping aesthetic matters in view. Beethoven’s transformations of Anton Diabelli’s waltz — which the composer described in a letter as a “SchusterFleck” (“cobbler’s patch”) — indulge in persiflage, irony, and parody, qualities that invite critical scrutiny. Beethoven was sometimes compared during his lifetime to Jean Paul, whose concept of humor as “the inverted sublime” and notion of a tensional duality of the Great and the Small applies well to Beethoven’s most paradoxical composition. How can we best shape this cycle as a whole in performance, while doing justice to its vivid contrasts and rich allusiveness? Numerous performance recommendations emerge from the integrated consideration of historical documents, musical analysis, and aesthetic reflection. Since the subject concerned here is animate rather than inanimate, it is not well grasped from just an objectivist, factual perspective.